(untitled) (Triyuga Academic Journal, 2021)
Recently, the use of ICT tools in teaching-learning has increased rapidly. The main objective of the research focused on the perspectives of teachers on the use of ICT tools and their effects on biology teaching. This study followed a quantitative survey research design. Altogether 55 biology teachers were selected from all the community and institutional schools of Siraha district where the science stream is running in classes 11 & 12. The data were collected through closed questionnaires and analyzed by using SPSS software like t-tests, mean, standard deviation and significance level. The data showed that almost all schools had minimum requirements of ICT tools. The majority of teachers had good knowledge about MS-applications, social sites and social media platforms, except one third didn’t know about it. Although the majority of biology teachers had poor practice about the use of ICT integrated in the classroom and they didn’t realize their pedagogical effects. Teacher’s level of qualification, ICT qualification and style of teaching etc., the independents were significantly associated with teachers ICT knowledge and ICT effects dependent factors. It is expected that the outcomes of this research provide proper information and suggestions to those who are responsible for integrating new technologies in school teaching particularly biology subjects.